2013
DOI: 10.1111/1469-0691.12265
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of Thin Layer Agar and Löwenstein–Jensen culture for diagnosis of tuberculosis

Abstract: Sputum smear microscopy for the diagnosis of tuberculosis (TB) is cheap and simple but its sensitivity is low. Culture on Löwenstein-Jensen (LJ) is more sensitive but it takes a long time to yield results. Thin-Layer Agar (TLA) culture was suggested as an equally sensitive and faster alternative. We evaluated the performance of TLA for diagnosing TB in Jogjakarta, Indonesia. People with suspected TB presenting from July 2010 to July 2011 to two chest clinics of the National TB Control Programme network of Jogj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…Moreover, microplates allow the microscopic detection of bacterial colonies before they can be seen with the naked eye, further decreasing the time to results. Previous studies have shown that M. tuberculosis can be detected on M7H11 from sputum samples as early as 7 days [29][30][31]. A meta-analysis of the results obtained with thin-layer agar and microscopicobservation drug susceptibility assays, in which patients' specimens are inoculated directly on drug-free and drugcontaining medium for DST, showed that the mean turnaround times for the two assays were 11.1 days (95% CI 10.1-12.0) and 9.9 days (95% CI 4.1-15.8), respectively [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microplates allow the microscopic detection of bacterial colonies before they can be seen with the naked eye, further decreasing the time to results. Previous studies have shown that M. tuberculosis can be detected on M7H11 from sputum samples as early as 7 days [29][30][31]. A meta-analysis of the results obtained with thin-layer agar and microscopicobservation drug susceptibility assays, in which patients' specimens are inoculated directly on drug-free and drugcontaining medium for DST, showed that the mean turnaround times for the two assays were 11.1 days (95% CI 10.1-12.0) and 9.9 days (95% CI 4.1-15.8), respectively [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, it was not possible to use microscopy to read the Lowenstein-Jensen tubes; therefore, microscopy was also not used to read the MOD9 plates, to maintain a similar method in the readings. Indeed, if we had used microscopy as for the thin-layer agar and microscopic observations of drug susceptibility protocols (14,15), this would have resulted in the rapid detection of microcolonies and thus rapid diagnosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de los buenos resultados de estos ensayos en la detección de individuos con infección tuberculosa latente, su utilidad en el diagnóstico de pacientes con enfermedad activa es escasa [17,28,29]. Pathan y colaboradores (2001) [30] reportaron una baja frecuencia de linfocitos T CD4 + secretores de IFN-γ específicos de ESAT-6 en individuos con tuberculosis activa, en comparación con aquellos con infección tuberculosa latente.…”
Section: Arend Y Colaboradores (2001)unclassified
“…El diagnóstico microbiológico convencional se basa en la detección del bacilo en al menos una de tres muestras de esputo recolectadas en tres días diferentes. Estas muestras se someten a tinción de ácido alcohol resistencia para evaluar al microscopio la presencia del microorganismo y se llevan a cultivo en medio Lowenstein-Jensen, lo cual es necesario para confirmar el diagnóstico [29].…”
Section: Diagnóstico De Tuberculosis Activaunclassified